Maternal Morbidities and Perinatal Outcomes of Delivery in Women with Preterm Prelabor Rupture of the Membranes (PPROM) - S Sallam (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Objective: This study was done to evaluate the maternal morbidities and perinatal outcomes of delivery in women with preterm pre-labor rupture of the membranes who delivered before and after 34 week along a period of five years in Al-Arish General Hospital. Methods:This  retrospective  study  involved  pregnant  women  with  a  singleton  pregnancy who  suffered  from  preterm  pre-labor  rupture  of  the  membranes. Maternal  morbidities  included chorioamnionitis  and  febrile  reaction,  umbilical  cord  prolapse,  and  puerperal  pyrexia,  while, neonatal  outcomes  comprised  neonatal  intensive  care  unit  (NICU)  admission  as  in  case  of neonatal sepsis or respiratory distress syndrome, neonatal jaundice, or eventual mortality. Results: A total of 443 eligible women were involved. The mean age of included women was 23.11 ± 3.8 years (range: 18 - 38 years). The mean gestational age at delivery was 23.17 ± .2 weeks (range: 21 - 36 weeks). The included women were divided into 2 groups: group I  n=232) including women who delivered at < 34 weeks of gestation; and group II (n=211) including women who delivered at ≥ 34 weeks of gestation. The rate of chorioamnionitis was significantly higher in women of group II [21 (9.95%) vs. 11 (4.74%), respectively, p=0.023].The rate of NICU admission for  neonatal  sepsis  was  significantly  higher  in  women  of  group  II  [32  (15.2%)  vs.  19  (8.2%)), respectively, p=0.018]. Conclusion: In case of PPROM, delivery after rather than before 34 weeks of gestation was linked to comparable rates of NICU admissions for neonatal RDS and jaundice with no statistically significant difference in perinatal mortality; yet with significantly higher rates of maternal morbidities as chorioamnionitis and neonatal sepsis.